Minangkabau Comedy Communication on Social Media: A Case Study of Praz Teguh's YouTube Channel (Oratio Directa, 2021)
Social media has changed the production, distribution, and reception of cultural messages. This study examines the communication process of Minangkabau comedy on Praz Teguh's YouTube channel, particularly content concerning modified public minibuses in Padang. The research uses a qualitative descriptive case-study method within a post-positivist paradigm. Data were obtained through interviews with Praz Teguh and three informants, observation of channel content, and document review. The findings show that the communication process begins with everyday Minangkabau experience, which is selected and transformed into a comedy script, produced as audiovisual content, and distributed through YouTube. Comedy reduces distance between communicator and audience, while cultural symbols provide recognition and context. Audience acceptance is supported by entertainment, agreement with the experience being represented, and the accessibility of the platform. The process integrates information, education, cultural representation, and economic incentives, but still requires accuracy and sensitivity toward the represented community.
Keywords: Comedy communication; Minangkabau culture; YouTube; Social media; Case study